Association of Volume Overload With Kidney Function Outcomes Among Patients With Heart Failure With Reduced Ejection Fraction - Wendy McCallum (Kidney International Reports, 2020)
Introduction: In patients with heart failure with reduced ejection fraction (HFrEF), volume overload is associated with mortality. Few studies that have examined the relation between volume and long-term kidney function outcomes in HFrEF. Methods: Using data from the Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study With Tolvaptan (EVEREST) trial, we used multivariable Cox regression models to evaluate the association between volume overload as evaluated by B-type natriuretic peptide (BNP) and N-terminal pro B-type natriuretic peptide (NT-proBNP), and a clinical congestion score (scale of 0–12) composed of pedal edema, jugular venous distension, rales, and orthopnea with the occurrence of estimated glomerular filtration rate (eGFR) decline by >40%, and incident chronic kidney disease (CKD) stage ≥4 defined by eGFR of <30 ml/min per 1.73 m2, over a median 10-month follow-up. Results: Among 3718 patients (mean eGFR 59 ± 22 ml/min per 1.73 m2), 340 (9%) reached an eGFR decline >40% and 337 (10%) developed incident CKD stage ≥4. In multivariable models, compared with those in the quartile of lowest NT-proBNP, those within the highest quartile had a significantly higher risk of eGFR decline by >40% (hazard ratio [HR] = 2.62 [95% confidence interval CI = 1.62, 4.23]) and incident CKD stage ≥4 (HR = 2.66 [95% CI = 1.49, 4.77]), with similar trends for BNP. Similarly in multivariable models, patients in the quartile of highest congestion score had a 48% increased risk for eGFR decline by >40% (HR = 1.48 [95% CI = 1.07, 2.06]) and a 42% increased risk for CKD stage ≥4 (HR = 1.42 [95% CI = 1.01, 1.99]), compared with the lowest quartile. Conclusion: Volume overload, as indicated both by elevated natriuretic peptides and clinical signs and symptoms, is associated with increased risk for clinically important kidney function outcomes in HFrEF.